The 8th Japan Bioanalysis Forum symposium. (December 2017) - Matsumaru, Takehisa
The 8th Japan Bioanalysis Forum symposium, the Tower Hall Funabori, Tokyo, Japan, 8–9 February 2017: The 8th Japan Bioanalysis Forum (JBF) symposium was successfully held between 8 and 9 February 2017 at the Tower Hall Funabori, Tokyo, Japan. In total, 24 speakers from Japan, USA and Europe gave presentations regarding the immunogenicity of biopharmaceuticals, ICH S3A Q&A microsampling, ICH M10 bioanalytical method validation, large molecule analysis through LC-MS, auditing activities for bioanalysis and biomarker bioanalysis. Achievements regarding eight diverse themes were also shared by Japan Bioanalysis Forum discussion groups. Over 300 scientists from regulatory agencies, industry and academia actively took part in discussions during the symposium. This article provides the highlights of all the topics discussed in this symposium.